Parental weight perceptions: a cause for concern in the prevention and management of childhood obesity in the United Arab Emirates. - Abdulla Aljunaibi (Public Library of Science (PLoS), 2013)
Parental participation is a key factor in the prevention and management of childhood obesity, thus parental recognition of weight problems is essential. We estimated parental perceptions and their determinants in the Emirati population. We invited 1541 students (grade 1-12; 50% boys) and their parents, but only 1440 (6-19 years) and their parents consented. Of these, 945 Emirati nationals provided data for analysis. Anthropometric and demographic variables were measured by standard methods. CDC BMI percentile charts for age and sex were used to classify children's weight. Parental perception of their children's weight status (underweight, normal, and overweight/obese) was recorded. Logistic regression analyses were used to identify independent predictors of parental perceptions of children's weight status. Of all parents, 33.8% misclassified their children's' weight status; underestimating (27.4%) or overestimating (6.3%). Misclassification was highest among parents of overweight/obese children (63.5%) and underweight (55.1%) children. More importantly, parental perceptions of their children being overweight or obese, among truly overweight/obese children, i.e. correct identification of an overweight/obese child as such, were associated with the true child's BMI percentile (CDC) with an OR of 1.313 (95% CI: 1.209-1.425; p<0.001) per percentile point, but not age, parental education, household income, and child's sex. We conclude that the majority of parents of overweight/obese children either overestimated or, more commonly, underestimated children's weight status. Predictors of accurate parental perception, in this population, include the true children's BMI, but not age, household income, and sex. Thus, parents having an incorrect perception of their child's weight status may ignore otherwise appropriate health messages.